Beyond Dreams: Do Sleep-Related Movements Contribute to Brain Development? - Blumberg, Mark S. (Frontiers in Neurology, 2010)
Conventional wisdom has long held that the twitches of sleeping infants and adults are by-products of a dreaming brain. With the discovery of active (or REM) sleep in the 1950s and the recognition soon thereafter that active sleep is characterized by inhibition of motor outflow, researchers elaborated on conventional wisdom and concluded that sleep-related twitches are epiphenomena that result from incomplete blockade of dream-related cortical activity. This view persists despite the fact that twitching is unaffected in infant and adults when the cortex is disconnected from the brainstem. In 1966, Roffwarg and colleagues introduced the ontogenetic hypothesis, which addressed the preponderance of active sleep in early infancy. This hypothesis posited that the brainstem mechanisms that produce active sleep provide direct ascending stimulation to the forebrain and descending stimulation to the musculature, thereby promoting brain and neuromuscular development. However, this hypothesis and the subsequent work that tested it did not directly address the developmental significance of twitching or sensory feedback as a contributor to activity-dependent development. Here I review recent findings that have inspired an elaboration of the ontogenetic hypothesis. Specifically, in addition to direct brainstem activation of cortex during active sleep, sensory feedback arising from limb twitches produces discrete and substantial activation of somatosensory cortex and, beyond that, of hippocampus. Delineating how twitching during active sleep contributes to the establishment, refinement, and maintenance of neural circuits may aid our understanding of the early developmental events that make sensorimotor integration possible. In addition, twitches may prove to be sensitive and powerful tools for assessing somatosensory function in humans across the lifespan as well as functional recovery in individuals with injuries or conditions that affect sensorimotor function.